2019
DOI: 10.1002/jcp.28872
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated microRNAs in colorectal carcinogenesis: New insight to cell survival and apoptosis regulation

Abstract: Colorectal cancer (CRC) is the third most common cancer and a leading cause of cancer-related death worldwide. About 1.8 million new cases were reported in 2018.Accordingly, there is an urgent need for development of effective strategies to lower the mortality and morbidity originated from this malignancy. MicroRNAs (miRNAs) play key roles in several cellular events. They have attracted a great deal of attention in the etiology of a variety of disorders including cancer and might be considered as disease bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 100 publications
0
17
0
Order By: Relevance
“…MicroRNAs (miRNAs) are a class of short noncoding RNAs that have emerged as significant epigenetic regulators of cellular functions, predominantly through silencing of their target genes via direct complementary mRNA 3′UTR base pairing [10]. Dysregulation of miRNAs has been reported in numerous cancers where individual miRNAs behave in an oncogenic or tumor suppressor manner [11][12][13][14]. To date, several profiling studies have reported that miRNAs are associated with clinical outcome in NB [15] and specific miRNAs have been identified to regulate key processes such as apoptosis, differentiation, cell proliferation and cell invasiveness in NB [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a class of short noncoding RNAs that have emerged as significant epigenetic regulators of cellular functions, predominantly through silencing of their target genes via direct complementary mRNA 3′UTR base pairing [10]. Dysregulation of miRNAs has been reported in numerous cancers where individual miRNAs behave in an oncogenic or tumor suppressor manner [11][12][13][14]. To date, several profiling studies have reported that miRNAs are associated with clinical outcome in NB [15] and specific miRNAs have been identified to regulate key processes such as apoptosis, differentiation, cell proliferation and cell invasiveness in NB [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs regulate the expression of target genes at the posttranscriptional level, and many miRNAs participate in the regulation of apoptosis (Anvarnia et al, 2019). We identified the possible miRNAs involved in the antiapoptotic effects of CTRP6 in salivary glands.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the underlying mechanism of SHU00238 in tumor suppression, miRNAs profiling was performed [32,33,34]. Several known tumor regulators are significantly regulated by SHU00238 treatment.…”
Section: Discussionmentioning
confidence: 99%